New perspectives in cardiovascular risk reduction: focus on HDL - Stefania Paolillo (Monaldi Archives for Chest Disease, 2015)
Cardiovascular diseases represent the leading cause of morbidity and mortality worldwide, mostly contributing to hospitalizations and health care costs. Dyslipidemias represent one of the major cardiovascular risk factor and its management, throughout life-style modifications and pharmacological interventions, has shown to reduce cardiac events. The risk of adverse cardiovascular events is related not only to elevated LDL blood levels, but also to decreased HDL concentrations, that exhibit protective effects in the development of atherosclerotic process. Aim of this review is to summarize current evidences about defensing effects of such lipoproteins and to show the most recent pharmacological strategies to reduce cardiovascular risk through the increase of their circulating levels.